A Review: The Fate of Bacteriocins in the Human Gastro-Intestinal Tract: Do They Cross the Gut–Blood Barrier? - Dicks, Leon M. T.; Dreyer, Leané; Smith, Carine; van Staden, Anton D. (Frontiers in Microbiology, 2018)
The intestinal barrier, consisting of the vascular endothelium, epithelial cell lining and mucus layer covers a surface of about 400 m2. The integrity of the gut wall is sustained by transcellular proteins forming tight junctions between the epithelial cells. Protected by three layers of mucin, the gut wall forms a non-permeable barrier, keeping digestive enzymes and microorganisms within the luminal space, separate from the blood stream. Microorganisms colonizing the gut may produce bacteriocins in an attempt to outcompete pathogens. Production of bacteriocins in a harsh and complex environment such as the gastro-intestinal tract (GIT) may be below minimal inhibitory concentration (MIC) levels. At such low levels, the stability of bacteriocins may be compromised. Despite this, most bacteria in the gut has the ability to produce bacteriocins, distributed throughout the GIT. With most antimicrobial studies being performed in vitro, we know little about the migration of bacteriocins across epithelial barriers. The behaviour of bacteriocins in the GIT is studied ex vivo, using models, flow cells, or membranes resembling the gut wall. Furthermore, little is known about the effect bacteriocins have on the immune system. It is generally believed that the peptides will be destroyed by macrophages once they cross the gut wall. Studies done on the survival of neurotherapeutic peptides and their crossing of the brain-blood barrier, along with other studies on small peptides intravenously injected, may provide some answers. In this review the stability of bacteriocins in the GIT, their effect on gut epithelial cells and their ability to cross epithelial cells are discussed. These are important questions to address in the light of recent papers advocating the use of bacteriocins as possible alternatives to, or used in combination with, antibiotics.